Sustainable value management - New concepts and contemporary trends - Dariusz Zarzecki; Marek Jabłoński (MDPI, 2020)
Sustainable value management reveals a new space for studying business models. The traditional approach is based on the assumption that the goal of any business is to make money. All decisions regarding supply and production should be made to maximize profit. The discrepancy in creating non-economic value is sometimes the result of separating ownership from control over an enterprise. Although shareholders are interested in maximizing profit, management that actually makes decisions can also pursue other goals. In addition to economic aspects, the management intentions of modern managers are also influenced by factors arising from the organizational culture built, co-created within the organization and sometimes with the participation of external actors such as suppliers and customers. The sources of the creation of social values will be the management intentions of top management, often initiated by the adopted values and rules on the basis of which resources are bound within the structure of the business model. The value of sustainability is based on the identification of those creative sources that relate to economic and social value. Economic value is created through social value and vice versa. This allows the complementarity of the value created to be mutually supportive. The business model that integrates both of these values should be more resistant to crises than the one that is oriented only toward producing economic value. Concurrent implementation of economic and social goals increases resilience and affects the success of modern business models. This is due to the specificity of the business ecosystem that is built as part of the business model, which, in essence, is based on the use of social factors to merge the business model into a complex ecosystem capable of producing value.
Keywords: 330